Late Holocene Aleppo pine (Pinus halepensis Miller) woodlands in Mallorca (Balearic Islands, Western Mediterranean): Investigation of their distribution and the role of human management based on anthracological, dendro-anthracological and archaeopalynological data. (20th August 2021) - Picornell-Gelabert, Llorenç; Servera-Vives, Gabriel; Carrión Marco, Yolanda; Burjachs, Francesc; Currás, Andrés; Llergo, Yolanda; Dufraisse, Alexa; De Luís Arrillaga, Martín; Mus Amézquita, Maurici
Abstract: The pioneering nature of Mediterranean pines and their phytosociological role have been largely discussed in relation to different agents (e.g., edaphic, climatic or anthropogenic). In this context, Aleppo pine is one of the most widespread pine species in the Mediterranean basin, as it is especially adapted to climatic constraints, such as drought and high seasonality, and has a high tolerance for salinity and strong coastal winds. It is also well adapted to regeneration after anthropogenic landscape disturbances, highlighting its important after-fire regeneration rates. In this sense, phytosociological studies conducted in Mediterranean landscapes have found that this species' wide distribution is mostly due to its rapid regeneration after human landscape transformation, including fire, and the abandonment of agricultural lands. Aleppo pine is considered to broadly develop after human action in sclerophyllous formation, in which it would be scarce or absent without human intervention. Parallel, paleoenvironmental and archaeobotanical studies have attempted to trace these trends back to prehistoric times to investigate this species' role in Late Pleistocene and Holocene vegetation and evaluate the role of climate and human action in its diachronic dynamics. In this study, we present a compendium of anthracological, dendro-anthracological and archaeopalyonological data with the objective of (i) investigating the nature and distribution of Aleppo pine on the island of Mallorca and (ii) evaluating the possibility that human action could have resulted in the spread of this pine species during the first two millennia of permanent human occupation of the island (c. 2300 cal. BCE–1st-century ACE). Investigating these archaeobotanical datasets, as well as making comparisons with anthracological and paleoenvironmental studies in neighbouring Mediterranean zones (Iberia), allowed us to attest that Aleppo pine is a natural, pre-human component of the Holocene vegetation of the island, and it is especially well-adapted to coastal environments. Moreover, we describe the trends and characteristics of the human management of pine woodlands through anthracology and dendro-anthracology, suggesting that human action did not provoke widespread growth of Aleppo pine in Mallorca at the expense of other vegetation types during prehistory. Such processes, well-documented by current phytosociological studies, probably began at some unknown point after the Romanisation of the island.